2016
DOI: 10.1080/02640414.2016.1265140
|View full text |Cite
|
Sign up to set email alerts
|

A knock to the system: A new sociotechnical systems approach to sport-related concussion

Abstract: Broader contextual factors that influence concussion management have tended to be overlooked. To address this, the present study used a sociotechnical systems approach to identify perceived responsibilities and applied strategies for three domains of concussion management (i.e., prevention, identification and treatment). Participants were 118 members of the community rugby union system in Australia (69.2% male). Participants from throughout the rugby system (e.g., players, parents, coaches, club management) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 23 publications
1
38
1
Order By: Relevance
“…The adoption of a complex systems thinking approach when attempting to understand elite sport performance is currently receiving traction in various sporting contexts (Cruickshank et al, 2015;Sadjad and Mitchell, 2016;Clacy et al, 2017;McLean et al, 2017;Mooney et al, 2017;Hulme et al, 2019a). In particular, it is recognized that sports organizations are characteristic of "complex sociotechnical systems, " and that a range of organizational factors interact to influence athlete performance (Fletcher and Wagstaff, 2009;Salmon, 2017;Rumbold et al, 2018;Hulme et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adoption of a complex systems thinking approach when attempting to understand elite sport performance is currently receiving traction in various sporting contexts (Cruickshank et al, 2015;Sadjad and Mitchell, 2016;Clacy et al, 2017;McLean et al, 2017;Mooney et al, 2017;Hulme et al, 2019a). In particular, it is recognized that sports organizations are characteristic of "complex sociotechnical systems, " and that a range of organizational factors interact to influence athlete performance (Fletcher and Wagstaff, 2009;Salmon, 2017;Rumbold et al, 2018;Hulme et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that there is greater value in studying sports systems as a "whole, " rather than evaluating the relative contribution of their constituent "parts" in isolation (Hulme and Finch, 2015;Kleiner et al, 2015). Accordingly, systems analysis methods have been applied to examine sports organizations and systems in areas such as football (McLean et al, 2017), rugby (Clacy et al, 2017), and distance running (Hulme et al, 2017(Hulme et al, , 2019a. Given the reported utility of such applications, further systems thinking methods and approaches in other sports contexts have been encouraged (Hulme et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Clacy et al, forthcoming;Salmon et al 2017a,b). McLean, Salmon, Gorman, Naughton and Soloman (Continental drift) describe an exploratory study in which social network analysis was used to examine differences in the passing sequences leading to goals scored by international football teams competing in the knock-out stages of the 2016 European football championships (EURO) and COPA America football championships (COPA).…”
Section: Introductionmentioning
confidence: 99%
“…The psychosocial impact of acculturation on incidence of reported SRC has not been widely researched, however some studies have demonstrated that athletes feel a pseudo‐cultural pressure to “play tough” and downplay injury based on the norms learnt through socialisation with their teammates and modelling from authority figures (Kerr, ; McCrea, Hammeke, Olsen, Leo, & Guskiewicz, ; Schinke, Hanrahan, & Catina, ; Wiese‐Bjornstal, ). Previous literature has identified the potential impact of this kind of sporting culture on reporting behaviours and treatment adherence (Clacy, Goode, Sharman, Lovell, & Salmon, ; Clacy, Goode, Sharman, Lovell, & Salmon, ; Hollis, Stevenson, McIntosh, Shores, & Finch, ). In the present study, immediate family member participation along with duration of sport participation did impact reported SRC incidence, which may suggest some sociocultural modelling effect in the incidence of SRC in junior athletes.…”
Section: Discussionmentioning
confidence: 99%